2007
DOI: 10.1093/pcp/pcm020
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-Phosphate Dehydrogenase Plays a Pivotal Role in Nitric Oxide-Involved Defense Against Oxidative Stress Under Salt Stress in Red Kidney Bean Roots

Abstract: The pivotal role of glucose-6-phosphate dehydrogenase (G-6-PDH)-mediated nitric oxide (NO) production in the tolerance to oxidative stress induced by 100 mM NaCl in red kidney bean (Phaseolus vulgaris) roots was investigated. The results show that the G-6-PDH activity was enhanced rapidly in the presence of NaCl and reached a maximum at 100 mM. Western blot analysis indicated that the increase of G-6-PDH activity in the red kidney bean roots under 100 mM NaCl was mainly due to the increased content of the G-6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
60
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(75 citation statements)
references
References 90 publications
10
60
0
3
Order By: Relevance
“…Because it is the first NADPHgenerating enzyme in the pentose phosphate pathway (WAKAO et al, 2008), G6PdH-deficient cells are highly sensitive to oxidative stress, in contrast to those expressing appropriate levels of enzyme activity (LIU et al, 2007). The fact that G6PdH is a regulatory enzyme in this oxidative pathway (TAIZ & ZEIGER, 2013) suggests that the stress caused by the temperatures during seed germination of M. brauna likely resulted in less available energy for biosynthetic processes during germination, owing to lower enzyme activity.…”
Section: Resultsmentioning
confidence: 99%
“…Because it is the first NADPHgenerating enzyme in the pentose phosphate pathway (WAKAO et al, 2008), G6PdH-deficient cells are highly sensitive to oxidative stress, in contrast to those expressing appropriate levels of enzyme activity (LIU et al, 2007). The fact that G6PdH is a regulatory enzyme in this oxidative pathway (TAIZ & ZEIGER, 2013) suggests that the stress caused by the temperatures during seed germination of M. brauna likely resulted in less available energy for biosynthetic processes during germination, owing to lower enzyme activity.…”
Section: Resultsmentioning
confidence: 99%
“…NaCl-induced NO synthesis was inhibited by the NOS inhibitor L-NAME in Atriplex centralasiatica (Xu et al 2011a), Olea europaea (Valderrama et al 2007), Phragmites communis (Zhao et al 2004), and Populus euphratica (Zhang et al 2007). In contrast, Liu et al (2007) reported that NO production, induced by 100 mM NaCl, was not affected by L-NAME in Phaseolus vulgaris. In Arabidopsis thaliana, Zhao et al (2007a) observed a reduced quantity of the NOA1 protein and decreased NO levels after being exposed to 100 mM NaCl for 2 h. AtNOAl {AtNOSl) was identified as a putative Arabidopsis NOS gene, because these Arabidopsis mutants were defective in NO accumulation in the roots (Guo et al 2003), but later it was found that AtNOSl had; no NOS activity in vitro.…”
Section: No Production In Plants Exposed To Naclmentioning
confidence: 88%
“…In contrast, higher activities of POX, APX, and GR were observed in the NO-deficient Atnoal plants, and these mutants also showed lower activities of SOD and CAT than wild-type plants under NaCl stress (Zhang et al 2010). 0.05 mM of SNP increased the activity of APX, whereas it decreased that of SOD and POD, and did not affect the activity of CAT in the roots of Phaseolus vulgaris plants exposed to high salinity (Liu et al 2007). The NO donor SNP can also control the level of non-enzymatic antioxidants, such as those of ascorbate or glutathione.…”
Section: No and Salt Tolerancementioning
confidence: 92%
“…4 Salt stress can lead to an accumulation of high levels of ROS, such as superoxide (O 2 -·), hydrogen peroxide (H 2 O 2 ) and hydroxyl radicals (OH·). 5,6 These may disturb cellular redox homeostasis, and then lead to oxidative damage. It has been shown that the AP may participate in the adaptation to salt stress since salt stress increased the activity of the AP.…”
mentioning
confidence: 99%